Peak locomotor intensity in elite handball players: a first insight into player position differences and training practices - Fleureau, A.; Rabita, G.; Leduc, C.; Buchheit, M.; Lacome, M. (The Journal of Strength and Conditioning Research, 2023)
The aims of the study were to (a) describe the peak locomotor intensity sustained during handball matches and (b) compare them with small-sided games (SSGs) programmed during training in elite handball players. Small-sided game (n = 342) and match (n = 121) data were collected among 11 players (25 ± 7 years, 191 ± 8 cm, 89 ± 12 kg) belonging to an elite French Handball team. Players' locomotor activity was recorded using 20-Hz Local Positioning System. Peak total (TD[m]) and high-speed running distance (HS[m]) and mechanical load (Accel`Rate [a.u.]) were calculated during different time periods (1-15 minutes different rolling averages). A plot of log (locomotor variables) against log (time) allowed to obtain a straight line with a slope and an intercept for each variable. Between-position differences during matches and difference between matches and SSGs were assessed with linear mixed model and magnitude-based decisions. Almost certainly higher peak locomotor intensity (intercept) was found in Wingers (TD: 156 ± 13; HS: 96 ± 12; Accel`Rate: 13 ± 3) compared with other playing positions for TD (Back players: 127 ± 10; Pivots: 136 ± 13), HS (Back players: 56 ± 9; Pivots: 57 ± 11), and Accel`Rate (Back players: 11 ± 2; Pivots: 11 ± 2). However, no clear between-position difference was found regarding the slope. Additionally, none of the SSGs format produced an overload in peak locomotor intensity in comparison with matches (TD: 138 ± 16; HS: 66 ± 20; Accel`Rate: 12 ± 2). Because reaching the peak locomotor intensity sustained during match is not possible using SSGs, practitioners should consider using isolated conditioning drills (e.g., short or long intervals, repeated sprints). Moreover, specific attention should be paid for Winger's work supplementation because they present the highest peak locomotor intensity in the team.